Manajemen Kompetensi Pedagogik - Mawardi Mawardi (STIE Syari'ah Al-Mujaddid Tanjung Jabung Timur, 2022)
This research aims for the pedagogical competency of teachers in learning process learning planning, and in improving students' learning motivation.To achieve these goals, this research uses a qualitative approach. Data collection techniques are performed through interviews, observations, and documentation studies.Data analysis procedures are data reduction, data presentation, and conclusion drawing.While the research subjects are principals, vice principals, and teachers The results show that: (1) Management of teacher pedagogical competencies in learning planning is done by drafting RPP, but some teachers do not bring RPP during the teaching learning process so that the learning objectives are not achieved to the maximum(2) The competency of the teacher's pedagogic in the learning process is carried out by deepening and establishing a number of learning materials as contained in the package book , as for the learning process there is poor class management and poor use of time; and (3) The competency of pedagogic teachers in improving student learning motivation is done by giving students the opportunity to be actively involved in using information and communication technology facilities in achieving learning objectives but not yet implemented to the maximum.